2022
DOI: 10.3389/fonc.2022.915240
|View full text |Cite
|
Sign up to set email alerts
|

RAC3 Inhibition Induces Autophagy to Impair Metastasis in Bladder Cancer Cells via the PI3K/AKT/mTOR Pathway

Abstract: BackgroundBladder cancer (BCa) is one of the most frequent malignant tumors globally, with a significant morbidity and mortality rate. Gene expression dysregulation has been proven to play a critical role in tumorigenesis. Ras-related C3 botulinum toxin substrate3 (RAC3), which is overexpressed in several malignancies and promotes tumor progression, has been identified as an oncogene. However, RAC3 has important but not fully understood biological functions in cancer. Our research aims to reveal the new functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…Figure b shows similar gene expression profiles for (i) cells cultured in stiff 3D conditions (“stiff to stiff”) and cells moved from stiff to soft 3D culture (“stiff to soft”) and (ii) cells cultured in soft 3D conditions (“soft to soft”) and cells moved from soft to stiff 3D culture (“soft to stiff”). Remarkably, the top three downregulated genes in conditions where cells experienced a stiff 3D microenvironment for any length of time were tumor suppressor genes LATS1 , BCAR3 , and CDKN2C . Of the top upregulated genes in stiff-primed conditions (log 2 fold-change >2, p -value < 0.05), several of these genes have been identified as prognostic markers in cancer, including SLC6A4 , MACC1 , SLC14A2 , CRB3 , NFKBIL1 , RAC3 , CLIC3 , CYBA , FRMD6-AS1 , LAIR1 , L1TD1 , SEMA3E , PCDH11Y , MIRLET7BHG , and TERC (Figure b). We performed GO Term analysis comparing cells primed in soft culture vs cells primed in stiff culture and note changes in terms including transcriptional misregulation in cancer, chromatin organization, nucleus organization, and metabolism of RNA, which may suggest epigenetic mechanisms act as a component responsible for some of these transcriptional changes (Figure S9). For the genes that may be correlated with mechanical memory, we examined TCGA for pancreatic cancer patient prognosis data .…”
Section: Resultsmentioning
confidence: 99%
“…Figure b shows similar gene expression profiles for (i) cells cultured in stiff 3D conditions (“stiff to stiff”) and cells moved from stiff to soft 3D culture (“stiff to soft”) and (ii) cells cultured in soft 3D conditions (“soft to soft”) and cells moved from soft to stiff 3D culture (“soft to stiff”). Remarkably, the top three downregulated genes in conditions where cells experienced a stiff 3D microenvironment for any length of time were tumor suppressor genes LATS1 , BCAR3 , and CDKN2C . Of the top upregulated genes in stiff-primed conditions (log 2 fold-change >2, p -value < 0.05), several of these genes have been identified as prognostic markers in cancer, including SLC6A4 , MACC1 , SLC14A2 , CRB3 , NFKBIL1 , RAC3 , CLIC3 , CYBA , FRMD6-AS1 , LAIR1 , L1TD1 , SEMA3E , PCDH11Y , MIRLET7BHG , and TERC (Figure b). We performed GO Term analysis comparing cells primed in soft culture vs cells primed in stiff culture and note changes in terms including transcriptional misregulation in cancer, chromatin organization, nucleus organization, and metabolism of RNA, which may suggest epigenetic mechanisms act as a component responsible for some of these transcriptional changes (Figure S9). For the genes that may be correlated with mechanical memory, we examined TCGA for pancreatic cancer patient prognosis data .…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have shown that RAC3 is involved in tumor invasion and metastasis 25 , 26 , which drove us to further investigate whether RAC3 played a role in NSCLC cells migration. When RAC3 was knocked down in lung cancer cells, the enhanced migration by CAFs was diminished.…”
Section: Resultsmentioning
confidence: 99%
“…RAC3 is highly expressed in bladder cancer cells, and stimulates proliferation and migration of bladder cancer cells via PYCR1-mediated JAK/STAT pathway activation 26 . Interestingly, when RAC3 was knocked down, the growth and migration of bladder cancer cells were inhibited through the PI3K/AKT/mTOR pathway-mediated autophagy induction 25 . RAC3 inhibition also caused a significant reduction of both invasion and adhesion of breast cancer cells through the ERK-2/NF-κB signaling pathway 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Among the 10 model genes, RAC3 stands out as one of the three isoforms within the Rho GTPase subfamily 29,30 . Studies have demonstrated that RAC3 enhances tumor cell proliferation, migration, and invasion by activating the JAK/STAT signaling pathway 31,32 . Furthermore, high expression of RAC3 predicts a poor prognosis of BLCA 33 .…”
Section: Discussionmentioning
confidence: 99%